DESAIN FISIK APLIKASI NOMOR ANTREAN PENDAFTARAN PASIEN RAWAT JALAN BERBASIS ANDROID DI PUSKESMAS NGANJUK - Erlinda Cahyani Puspita Sari; Chyntia Vicky Alvionita (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2021)
Queue theory is a theory that concerns the mathematical study of queues or rows. waiting. A queue is a collection of entries or objects waiting for service. Before the patient or The patient's family registering is expected to take a conventional queue number. This causes the patient and the patient's family have to queue for a long time. In addition, patients and their families who registering with a very large number of people there will be a dense crowd. This research design uses quantitative descriptive by using a design assessment questionnaire physical android based outpatient registration queue number application. Descriptive quantitative method for produce descriptive data in the form of scoring or assessment of the results of research respondents' questionnaires. The results of this study obtained the physical design of the -based Outpatient Registration Queue Number application android for Nganjuk Health Center Patients. The physical design of the android-based outpatient registration queue number application at the puskesmas nganjuk can make it easier to build applications.